KAMU SPOR ÖRGÜTLERİNDE YENGEÇ SEPETİ SENDROMU VE ÖRGÜTSEL ADALET ALGI DÜZEYİNİN ÖRGÜTSEL ÖZDEŞLEŞMEYE ETKİSİ: ÖRGÜT İKLİMİNİN ARACI ROLÜ - ŞAHİN, MEHMET (Fırat Üniveristesi, 2025)
Günümüzde sporun birey ve toplum sağlığının iyileştirilmesinde ve ulusların sosyal, kültürel ve ekonomik kalkınmasında oynayabileceği rolün büyüklüğü yadsınamaz bir gerçekliktir. Spor hizmetlerinin bu minvalde sağlıklı ve etkin bir şekilde halka sunulmasının ön koşulu Türkiye'de sporu yöneten kurum olan Gençlik ve Spor Bakanlığı'nın adil yönetilmesi ve çalışanlarının kurumla özdeşleştiği bir ortamın sağlanmasına bağlıdır. Personellerin kendinden daha başarılı olanlara yetişemeyeceğini anlayınca onları aşağı çekmeyi hedef alan, olumsuz davranış ve tutumları içeren kültürel bir eğilim olan yengeç sepeti sendromu ve örgütsel adalet gibi örgütüyle özdeşleşmesinin seviyesini etkileyen durumların, sağlanan olumlu örgüt iklimi ortamıyla minimize edilerek örgüt lehine bir davranışa dönüştürülmesi sporun geleceği açısından önem arz etmektedir. Bu çalışmanın öncelikli amacı gençlik ve spor il müdürlüklerinde görevli personelin yengeç sepeti sendromu ve örgütsel adalet algı düzeyinin örgütsel özdeşleşmeye etkisini belirlemek ve bu etkide örgüt ikliminin aracı rolünü saptamaktır. Çalışmanın evrenini Türkiye genelinde faaliyetlerini sürdüren Gençlik ve Spor Bakanlığı'na bağlı taşra teşkilatlanmasında yer alan gençlik ve spor il müdürlüklerinde görevli (657 sayılı kanuna tabi memur personel) (n: 21.414) personeli oluşturmakta olup, örneklemini ise bu kurumlarda çalışan personelden rasgele örnekleme yöntemi ile ulaşılmış 1.087 çalışan oluşturmaktadır. Çalışmamızda nicel araştırma yöntemiyle yapılan ilişkisel tarama modeli kullanılmıştır. Verilerin elde edilmesinde önceden geçerlik ve güvenirliği tespit edilmiş, "Yengeç Sepeti Sendromu Ölçeği", "Örgütsel Adalet Ölçeği", "Örgütsel Özdeşleşme Ölçeği" ve "Örgüt İklimi Ölçeği" ölçek formu kullanılmıştır. Verilerin analizi IBM SPSS (25.0) veri analiz programı ile yapılmış olup ölçekler arasındaki ilişkinin varlığını ve moderasyon etkilerini incelemek için process makro (model 4) kullanılmıştır. Çalışma sonunda, örgütsel adaletin örgütsel iklim ve özdeşleşme ile pozitif bir ilişkiye sahip olduğunu ancak, yengeç sepeti sendromunun örgütsel iklim ve özdeşleşme üzerindeki etkilerinin sınırlı olduğu belirlenmiştir. Aynı zamanda örgütsel iklimin örgütsel özdeşleşme üzerinde güçlü ve anlamlı bir etkiye sahip olduğunu, dolayısıyla iklimin özdeşleşmede önemli bir belirleyici olduğu tespit edilmiştir. Çalışmada sağlanan veriler ışığında gençlik ve spor il müdürlüklerinde görevli personellerin yengeç sepeti sendromu ve örgütsel adalet gibi örgütüyle özdeşleşmesinin seviyesini etkileyen durumların, sağlanan olumlu örgüt iklimi ortamıyla minimize edilerek örgüt lehine bir davranışa dönüştürülmesi sporun geleceği açısından önem arz etmektedir.

Today, it is an undeniable reality that sports can play an important role in the improvement of individual and public health and in the social, cultural and economic development of nations. The prerequisite for the provision of sports services to the public in a healthy and effective manner in this regard is the fair management of the Ministry of Youth and Sports institution that manages sports in Turkey and the provision of an environment in which its employees identify with the institution. It is important for the future of sports that the situations that affect the level of identification with the organization, such as the crab basket syndrome, which is a cultural tendency that includes negative behaviors and attitudes that aim to pull down the employees when they realize that they cannot catch up with those who are more successful than themselves, and organizational justice, are minimized with the positive organizational climate environment provided and turned into a behavior in favor of the organization. The primary purpose of this study is to determine the effect of crab basket syndrome and organizational justice perception level of the personnel working in the provincial directorates of youth and sports on organizational identification and to determine the mediating role of organizational climate in this effect. The population of the study consists of the personnel working in the provincial directorates of youth and sports (civil servant personnel subject to the law numbered 657) (n: 21.414) in the provincial organization of the Ministry of Youth and Sports, which continues its activities throughout the Türkiye, and the sample consists of 1.087 employees reached by random sampling method from the personnel working in these institutions. In our study, the relational survey model with quantitative research method was used. "Crab Basket Syndrome Scale", 'Organizational Justice Scale', 'Organizational Identification Scale' and 'Organizational Climate Scale' scale forms, the validity and reliability of which were previously determined, were used to obtain the data. Data analysis was performed with IBM SPSS (25.0) data analysis program and process macro (model 4) was used to examine the existence of the relationship between the scales and moderation effects. At the end of study, ıt was determined that organizational justice has a positive relationship with organizational climate and identification, but the effects of crab basket syndrome on organizational climate and identification are limited. At the same time, it was found that organizational climate has a strong and significant effect on organizational identification, thus climate is an important determinant of identification. In the light of the data provided in the study, it is important for the future of sports that the situations that affect the level of identification with the organization, such as crab basket syndrome and organizational justice, of the personnel working in the provincial directorates of youth and sports are minimized with the positive organizational climate environment provided and turned into a behavior in favor of the organization.
Crab basket syndrome in public sport organizations and the effect of organizational justice perception level on organizational identification: The mediating role of organizational climate
Keywords: Spor